Strength and compressibility of organic soil stabilised with Mg-rich gypsum and concrete waste - Khairun Najihah, Kamarudin; Nurmunira, Muhammad; Almsedeen, Ayah; Mohd Fakhrurrazi, Ishak (Emerald Publishing, 2026)
Peat soils, common along Malaysia’s coastline, present geotechnical challenges due to low shear strength, high organic content, and high compressibility. Traditionally, chemical stabilisation methods using additives like Ordinary Portland Cement (OPC) and lime have been employed to enhance soil properties. However, the rising cost of these additives and their adverse environmental impact, particularly the carbon footprint of OPC, necessitate more sustainable alternatives. This study explores the use of industrial by-products and institutional waste, specifically Mg-rich gypsum (G) and concrete waste aggregate (CW), as eco-friendly additives for peat soil stabilisation. A comprehensive characterisation of the peat soil, including its physicochemical, mechanical, and morphological properties, was conducted. The soil was mixed with 5%, 10%, 15%, and 20% of G and CW by weight, and unconfined compressive strength tests were performed after 7 and 28 days of curing. Results indicated a significant improvement in shear strength, with values reaching up to 440 kPa after 28 days. Oedometer tests further revealed enhanced compressibility properties. The findings demonstrate that using G and CW not only improves the mechanical properties of peat soils but also promotes environmental sustainability through the recycling of industrial waste. This approach offers an innovative, cost-effective solution to managing problematic soils, reducing the need for traditional chemical stabilisers while contributing to waste reduction and carbon footprint minimisation.